ANALISIS PENGARUH KUALITAS PRODUK DAN PELAYANAN TERDAHAP KEPUASAN KONSUMEN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS DI TWISSTERDOG DENPASAR - Devika Inten A, I.G.A; Hartiati, Amna; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
This study aims to determine the attributes that are considered important by consumers to achieve customer satisfaction, determine the level of performance in Twissterdog , know the level of satisfaction or level of consumer suitability of products and services in Twissterdog , and determine the attributes that need to get priority from the company to achievement of customer satisfaction. This research was conducted in Twissterdog with the sample used was 97 respondents by using purposive and accidental sampling method. Data obtained from the questionnaire distribution were analyzed by Importance Performance Analysis method. The result of research shows that attribute with highest level of customer satisfaction on product quality is clarity of name and logo of company with satisfaction level 222%, attribute with lowest satisfaction level is price match with consumer interest, food presentation and price match with product quality with satisfaction level equal to 80.84%. Attributes with the highest level of customer satisfaction on the quality of service is the hospitality of the waiter and the courtesy of the waiter with a satisfaction level of 218%. Attribute with the lowest level of customer satisfaction on the quality of service is the convenience of café with a satisfaction level of 43%. Attributes that should be prioritized on product quality are price conformity with consumer interest, food presentation and price conformity with product quality. The attributes that must be prioritized on the quality of service is the ease of reaching the location, the cleanliness of the cafe, the availability of parking facilities and the convenience of the cafe. Keywords : Customer satisfaction, Importance Performance Analysis , Twissterdog .